Language Contact Phenomena: A Case Study of Indonesian-English Code-Switching in Social Media Communication: Language Contact Phenomena: A Case Study of Indonesian-English Code-Switching in Social Media Communication - Muhammad Adha Manuhutu; Ananda Intan Rahmadani; I Putu Eka Suardana (Universitas Bali Dwipa, 2024)
This study examines the phenomenon of Indonesian-English code-switching in social media communication, focusing on patterns, motivations, and sociolinguistic implications. Through analysis of social media posts across multiple platforms, this research identifies common patterns of code-switching and explores how bilingual Indonesian speakers navigate between languages in digital spaces. The findings suggest that code- switching serves various pragmatic and social functions, reflecting both linguistic competence and cultural identity in the modern Indonesian digital landscape. This research investigates Indonesian-English code-switching in social media, emphasizing patterns, motivations, and sociolinguistic implications. By analyzing posts across diverse platforms, it identifies recurring linguistic patterns and uncovers how bilingual Indonesian speakers dynamically alternate between languages in digital contexts. This study examines Indonesian-English code-switching in social media communication, focusing on its patterns, motivations, and sociolinguistic implications. Through an analysis of posts across diverse platforms, it identifies recurring linguistic trends and explores how bilingual Indonesian speakers fluidly alternate between languages in digital contexts.